Epithelioid Myofibroblastoma in an Old-Male Breast: A Case Report with MRI Findings - Seyma Yildiz; Zuhal Gucin; Ezgi Basak Erdogan (Case Reports in Radiology)
Myofibroblastoma of the breast (MFB) is a very rare benign stromal tumor. In recent years, increase in mammographic screenings has resulted in increased diagnosis of MFB. Most cases are old males and postmenopausal women. MFB may be confused as malignant, clinically, morphologically, or by imaging. Immunohistochemistry is essential for final diagnosis in these cases. We report a case of a pathologically diagnosed MFB in an 80-year-old male patient who had coexisting prostate cancer and describe its imaging characteristics, especially magnetic resonance imaging (MRI). In this paper, histopathological and MRI findings of the MFB were discussed.